PENYAMPAIAN INFORMASI DARI HUMAS PEMERINTAH DAN PEMBERITAAN MEDIA (ANALISIS KEY MESSAGES SIARAN PERS KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN NASIONAL DAN PEMBERITAAN KURIKULUM 2013 SELAMA APRIL-MEI 2013 DI KOMPAS, REPUBLIKA, DAN ANTARANEWS.COM) - Ika Karlina (Jurnal Universitas Paramadina, 2014)
One of the most significant activities in government media relation issupplying the information to the press. This research is aimed to identifygovernment public relations' performance in supplying information for thepress and whether the key messages is published by them. The methodologyof this research is quantitative content analysis on news release and newscoverage in three major media (Kompas, Republika, and Antaranews.com)about National Curriculum 2013 between April-May 2013. The issues aboutcurriculum 2013 is chosen because it's controversial and getting intensivereportage from the press. The result showed that there is a differencebetween the news releases and news coverage on media specifically on thetopics, key messages, and tone. Besides, media relations activity that hasbeen done by the Kemdiknas public relations cannot counter the negativepublicity about Curriculum 2013. This research also showed thatgovernment public relations is still focusing on persuasion and developingand protecting positive institutional images rather than providing theinformation for its public as obliged by the Law No. 14/2008 on Transparencyof Public Information (UU KIP).